Effects of Concentration of Pore Solution on Stability of Ion-Absorbed Rare Earth Ore Aggregate - Jie Wang; Guanshi Wang; Bengen Hong (Advances in Civil Engineering)
The continuous change in solution concentration in ore pores during in situ mineral leaching influences the stability of ore aggregate. In this study, influences of the concentration of ammonium sulfate ((NH4)2SO4) solution on the interaction forces between ore particles were calculated. On this basis, the mechanism by which (NH4)2SO4 solution concentration influences the stability of ore aggregate was analyzed. Furthermore, an empirical formula for estimating the critical (NH4)2SO4 solution concentration for aggregation and dispersion of ore body aggregates with different grain composition was proposed. Some major conclusions were drawn. First, for ore bodies with an initial particle size of less than 0.075 mm, the interaction force between particles was net attraction, with the distance range of this force increasing as the concentration of (NH4)2SO4 solution increased from ≤0.001 to 0.16 mol·L−1, aggregation of ore particles occurring within this distance range. Secondly, for ore bodies with initial particle size of less than 0.075 mm, the interaction force between particles was net attraction, but with the distance range of this force decreasing when the (NH4)2SO4 solution concentration increased from 0.16 to 0.28 mol·L−1, dispersion of ore particles occurring beyond this distance range. Thirdly, for ore bodies with particle sizes of less than 0.038, 0.075 and 0.1 mm, the cation exchange capacity (CEC) was 9.13, 8.96, and 8.8 cmol·kg−1, respectively, and the critical (NH4)2SO4 solution concentration affecting the aggregation and dispersion of ore bodies was 0.12, 0.16, and 0.20 mol·L−1, respectively.